Thermal aggregation of hen egg white lysozyme: effect of polyamines - Nobakht Motlagh Ghochani, Bi Bi Fatemeh; Moosavi-Nejad, Seyedeh Zahra (Archives of Advances in Biosciences, 2013)
Protein aggregation is a serious problem for both biotechnology and cell biology. Diseases such as prion misfolding, Alzheimer’s, and other amyloidosis are phenomena for which protein aggregation in our living cells is of considerable relevance. Human lysozyme has been shown to form amyloid fibrils in individuals suffering from nonneuropathic systemic amyloidosis, all of which have point mutations in the lysozyme gene. In this study, we investigated effect of small additives on the thermal aggregation of lysozyme. The main finding of this work is that multiple amine groups, spermine and spermidine, play pivotal roles in preventing the thermal aggregation of lysozyme. Our results showed that effect of spermine is more than spermidine.